Fuzzy Supervision of an Industrial Production Process by Extracting Experts Knwoledge, ISSN / ISBN 2308-4375 / 978-1-61208-620-0 - Hanane Zermane (eKNOW 2018 International Conference on Information, Process, and Knowledge Management,Rome, Italie, 2018)
The automation of production systems has been an answer to the changing and competitive industrial context and works by extracting data and experiences of experts. This automation is a double-edged sword; on one hand, it increases the productivity of the technical system (cost reduction, reliability, availability, quality), but, on the other hand, it increases the complexity of the system. This has led to the need of efficient technologies, such as Supervisory Control and Data Acquisition (SCADA) systems and techniques that could absorb this complexity such as artificial intelligence and fuzzy logic. In this context, we develop an application that controls the pretreatment and pasteurization station of milk localized in Batna (Algeria) by adopting a control approach based on expert knowledge and fuzzy logic.